Iman Restoration Therapy(IRT): A new counseling approach and it's usefulness in developing personal growth of Malay adolescent clients - Abdul Razak, Abdul Latif; Mohamad, Mardiana; Alias, Alizi; Mohd Kassim, Nordinah (s.n, 2012)
Over the years, it has become a trend that those in mental health professions, especially counselors and psychologists are less religious and some, atheistic, due to their secular belief system. This is coupled with their diminutive effort to link spirituality and science in most of their research works and intellectual framework in relation to counseling and treating psychological illness. However, it has been found in recent past that some counselors in their research studies reported using spirituality as an intervention tool, though, among participants with secular and Christian belief system